Oesophagus 2017
DOI: 10.1136/gutjnl-2017-314472.358
|View full text |Cite
|
Sign up to set email alerts
|

PWE-113 Comparing barium swallow with high resolution manometry in the diagnosis of primary oesophageal dysmotility – a retrospective study in a tertiary centre

Abstract: IntroductionThe gold standard for diagnosis of primary oesophageal dysmotility (POD) is high-resolution manometry (HRM). Barium swallow (BS) studies remain integral to many diagnostic algorithms for dysphagia. Our aim was to assess the sensitivity and specificity of BS in the diagnosis of POD including achalasia as defined using HRM.MethodPatients that had a BS and HRM within a year of each other over a period of 10 years were identified. Those with a history of upper gastrointestinal surgery were excluded. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…It is important to note that in 19.4% patients diagnosed with achalasia based on HRM findings, the barium study reported the presence of some other non-specific motility disorders. These findings were consistent with studies performed by El-Takli et al, in which the diagnosis of 42% patients with achalasia was missed by barium and by Schima et al, in which barium swallow correctly identified 58% of the cases diagnosed monometrically [4][5][6][7][8][9][10][11][12][13][14][15]. The low sensitivity of barium esophagram was attributed to the absence of the characteristic radiographic findings in most of the cases [4].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is important to note that in 19.4% patients diagnosed with achalasia based on HRM findings, the barium study reported the presence of some other non-specific motility disorders. These findings were consistent with studies performed by El-Takli et al, in which the diagnosis of 42% patients with achalasia was missed by barium and by Schima et al, in which barium swallow correctly identified 58% of the cases diagnosed monometrically [4][5][6][7][8][9][10][11][12][13][14][15]. The low sensitivity of barium esophagram was attributed to the absence of the characteristic radiographic findings in most of the cases [4].…”
Section: Discussionsupporting
confidence: 91%
“…Barium swallow reveals a classic bird-beak appearance due to narrowing at the gastroesophageal (GE) junction and proximal dilation of the aperistaltic esophagus [ 4 ]. Recent studies have proven that high-resolution esophageal manometry (HRM) should be the diagnostic test of choice for primary esophageal dysmotility disorders [ 5 ].…”
Section: Introductionmentioning
confidence: 99%